Theoretical review on the relationship between pedestrian infrastructure design and passenger ridership under rail-based transit oriented development - Nik Othman, Nik Nurul 'Aziemah; Jaafar Sidek, Mohd Farid; Kadar Hamsa, Abdul Azeez (2015)
Design of pedestrian infrastructure is one of few elements in relationship to Transit-oriented Development (TOD). The success of TOD depends on how effectively pedestrian network or link between transit station and surrounding land use. Literature stated that urban design factors and pedestrian-friendly design are positive planning factors in reducing automobile use through the reduction of automobile traffic speed and enhancing pedestrian accessibility to a transit center under TOD. In addition, the high vehicle ownership and increasing in population has led to an increasing in travel demand in most of the cities. The increasing use of private vehicles in the cities has affected the urban mobility of people significantly. To improve the mobility of the people, it is very important to provide efficient, attractive and reliable public transportation system to shift from the use of private to public transport. Moreover, MRT, LRT, monorail are some of the rail based transit system that would help to ease the movement of the commuters. However, the use of these public transit systems are basically depends very much on the number of passenger ridership. The rail network system of LRT has to consider all groups of users by providing facilities for elderly, physically disable and children. At many transit station the existing use of pedestrian infrastructure are not fully utilized due to lack of pedestrian infrastructure design. Therefore, pedestrian infrastructure design is one of many factors that contribute to the increase in passenger ridership at transit station by the provision of pedestrian infrastructure that are able to facilitate users to access the station. The purpose of this paper is to discuss on the role of pedestrian infrastructure on the use of public transport system from literature review. The description on the pedestrian infrastructure, movement of pedestrian and the use of public transport system are also explained in this paper. Finally, the major findings on the relationship between the pedestrian infrastructure and passenger ridership based on the literature review are also highlighted in this paper.